OPTIMASI DIAMETER PIPA PADA SISTEM JARINGAN AIR BERSIH DENGAN MENGGUNAKAN LINEAR PROGRAMMING DI KECAMATAN TUREN MALANG - Putra Permana, Rega; Saleh, Chairil (Media Teknik Sipil, 2014)
OPTIMASI DIAMETER PIPA PADA SISTEM JARINGAN AIRBERSIH DENGAN MENGGUNAKAN LINEAR PROGRAMMINGDI KECAMATAN TUREN MALANGRega Putra Permana1, Chairil Saleh21,2Jurusan Teknik Sipil Fakultas Teknik – Universitas Muhammadiyah MalangAlamat korespondensi : Jalan Raya Tlogomas 246 Malang 65144ABSTRACTTuren districts is one of 33 districts in Malang regency. Located ± 16 km east of the capitalcity of Malang (Kepanjen) and ± 26 km south of Malang. One of the factors that determine thelevel of performance of the system of providing clean water is effectiveness network.Results ofthe evaluation of the performance of a network of water pipes are clean before it shows that therelative energy level at each node the pipe showed a huge differenceLinear programming is a method which is very popular and reliable in solving optimizationproblem that contain linear function.Besides the simplicity of its functions, the ease factor insolving the equation system makes the linear programming more interesting to be applied insolving various optimization cases.This project to find out the level of linear programming to solving optimization problemsdiameter pipelines in the water distribution system.The results of the analysis Indicates that themodel linear programming is quite consistent and can provide optimum solutions appropriateobjective function and constraint functions of the set.Keywords: linear programming, diameter, pipe networks, optimization.